ASAS-ASAS BANTUAN HUKUM DAN PERAN HAKAM DALAM PENEGAKAN HUKUM: STUDI KRITIS ATAS TAFSIR AL-QURAN SURAT AL-NISÃ‚â€™ AYAT 35: Legal Aid Principle and Ḥakam Role in Law Enforcement: a Critical Interpretation of Surah al-Nisā’ Verse 35 - Kusnadi, Didi (Asy-Syari'ah, 2016)
This paper explains the bases of legal aid in Islamic law through a critical study on the concept of hakam reduced from the Quranic interpretation Surah al-NisÃ¢â€™ verse 35. As a primary source of Islamic law, the Quran is believed guarantying the universal principles of Islamic law that is relevant with law enforcement. It is also implemented practically and comprehensively in the line of the bases of legal aid and developed it into the concept of hakam. Therefore, it can be seen as one of Islamic law contribution within the rule of law in Indonesia through the concept of hakam which can be formed for development of legal aid concept and its application within the law of legal aid in Indonesia.